Influence of the 8-quinolinol concentration and solution pH on the interfacial properties of self-healing hydrotalcite coating applied to AZ31 magnesium alloy. (March 2021) - Anjum, Muhammad Junaid; Zhao, Jingmao; Tabish, Mohammad; Murtaza, Hassan; Asl, Vahdat Zahedi; Yang, Qiuxiang; Malik, Muhammad Uzair; Ali, Hamid; Yasin, Ghulam; Khan, Waheed Qamar
Graphical abstract: Abstract: The hydrotalcite-like (HT) coatings can provide an enhanced interfacial barrier to protect Mg alloys from corrosion. Therefore, 8-quinolinol (8Q), a green corrosion inhibitor, was intercalated in MgAl-based HT with varying concentration and pH values. The results revealed that the corrosion resistance was significantly improved when the pH of the solution was maintained at 10 with a 0.30 M concentration of 8Q. The hydrophobicity was also introduced to MgAl HT with the intercalation of 8Q, which was retained even after the long immersion. Furthermore, the self-healing performance of 8Q-intercalated HT was confirmed by single-frequency electrochemical impedance spectroscopy (EIS), which is a suitable method for in-situ evaluation of self-healing herein reported for the first time to evaluate the HT coatings. This thorough investigation of the hydrophobic MgAl HT coating is meaningfully supportive for researchers and engineers to have a deep understanding of its possibility for real-world applications in the area of corrosion and prevention.